Reader Response: Association of Self-reflection With Cognition and Brain Health in Cognitively Unimpaired Older Adults. (31st January 2023) - Daly, Timothy
Abstract : I have some issues with the claim of Demnitz-King and colleagues 1 that longitudinal and interventional studies are warranted to explicate whether self-reflection helps preserve cognition in older adults. Their assertion draws on the association of self-reflection with better global cognition and glucose metabolism and limited evidence that relationships are independent from health and lifestyle behaviors. The authors use a modified lifestyle for brain health (LIBRA) index, which provides a dementia risk score defined by empirical evidence and expert consensus.